The Outcomes of Surgical Treatment of Recurrent Lumbar Disk Herniation with Discectomy Alone and Discectomy with Posterolateral Interbody Fusion - Nayeb Aghayee, Hossein; Azhari, Shirzad; Heidarnejad, Farshad (Novelty in Biomedicine, 2014)
Background: Recurrent lumbar disk herniation (RLDH) is one of the major causes of failure of standard discectomy. The optimal treatment method for RLDH is controversial. In the current study, we aimed to compare the clinical and functional outcomes of treating RLDH with discectomy alone and discectomy associated with posterolateral interbody fusion (PLIF). Material and Methods: There were 41 patients with RLHD after primary discectomy in the current retrospective study. Patients were assigned to 2 groups based on the surgical method: discectomy alone (17 patients) and discectomy with PLIF (21 patients). At the final visit the following variables were measured and compared between groups: the back and radicular pain intensity using visual analogue scale (VAS), functional outcome using oswestry low back pain disability scale (ODI), return to previous work and complication. Patients were followed for 13.9±2.8 and 15±3 months in discectomy alone and discectomy with PLIF groups, retrospectively. Results: Complete fusion was achieved in 24 patients of PLIF group. The back pain intensity was the same; however the radicular pain intensity was significantly lower in PLIF group (1.5±0.9 V.s 2.3±1; p=0.017). Also, the mean of ODI scale was the same. 82.3% of patients in discectomy group and 87.5% of patients in PLIF group returned to previous work and the difference was not significant. One patient in discectomy group and 2 patients in PLIF group developed temporary neurological deficit which disappeared after 3 months. Conclusions: Although both discectomy alone and discectomy with PLIF were associated with favorable mid-term results in treating patients with RLDH, however, the authors recommend using discectomy with PLIF for lower radicular pain.